Analisis Pemanfaatan Media Pembelajaran Youtube Pada Mata Pelajaran Sejarah Kebudayaan Islam - Laily Syarifatul Hani; Bakti Fatwa Anbiya (Center of Education Journal (CEJou), 2023)
This research aims to describe the utilization of online learning media based on the YouTube platform in the subject of Islamic Cultural History at MA NU 03 Sunan Katong. The approach used is a qualitative approach with a descriptive method. The data collection techniques used are observation, interviews, and documentation. The results of the study show that the utilization of online learning media based on the YouTube platform can provide convenience for teachers and students in the learning process. Among them, the media can create a quiet and conducive classroom atmosphere, facilitate students' understanding of learning material that requires event visualization, reduce students' confusion, and create an interesting and engaging learning atmosphere. Therefore, the use of online learning media in the form of YouTube videos can be an effective alternative in realizing interactive and engaging learning.